Anisotropy in the mechanical behavior of Ti6Al4V electron beam melted lattices. (September 2019) - Jenkins, Sarah N.M.; Oulton, Thomas H.; Hernandez-Nava, Everth; Ghadbeigi, Hassan; Todd, Iain; Goodall, R.
Highlights: Conventional diamond lattices are distorted to produce novel anisotropic structures. These forms allow investigation of the anisotropy of lattices in additive manufacture. No mechanical anisotropy found in electron beam melted Ti6Al4V lattices. Abstract: With advances in additive manufacturing methods for metals with defined, complex shapes, the investigation of metallic lattice materials (metals with significant porosity and a regular arrangement of the solid, frequently in the form of thin struts) has become more common. These materials may be highly optimized for particular applications, and can show mechanical behaviors not displayed by other solids; for this reason, they are often used as routes to create mechanical metamaterials. However, thermal history experienced by the material in this novel process affects the microstructure produced, in particular making it highly directional. While understood for dense parts, the behavior in porous materials, where the structure itself can alter the thermal history experienced locally, is more ambiguous. This paper examines the mechanical properties of titanium alloy lattices based on the widely-used diamond structure, fabricated by electron beam melting (EBM). Related forms, distorted to alter the symmetry (from cubic to tetragonal) are tested and compared to more clearly elucidate the anisotropy in their mechanical properties. For the distorted lattices, the elastic modulus along the stretched direction is increased by a factor of over three, and the yield strength is more than doubled. In both lattices the orientation is found to have a much less significant effect than seen for bulk materials, likely to be due to the high proportion of the lattices that are influenced by free surface.